FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PETANI KAKAO DI DESA PADANG KAMBURI KECAMATAN BUPON KABUPATEN LUWU - Irmayani Irmayani (Jurnal Saintifik (Multi Science Journal), 2023)
Income is all receipts in the form of money or in the form of goods originating from other parties or industrial products which are valued on the basis of an amount of money from assets that are in effect at that time. Income is a person's source of income to meet the needs of daily life and is very important for the survival and livelihood of a person directly or indirectly. The purpose of this research is to find out whether capital, labor, land area and selling price affect the income of kdakao farmers in Padang Kamburi Village, Bupon District, Luwu Regency and to find out how much the net income of cocoa farmers is in Padang Kamburi Village, Bupon District, Luwu Regency. The type of research used is quantitative, with data collection methods namely observation, interviews, documentation and questionnaires. The data obtained in this study were then analyzed and processed based on the research objectives to be achieved. The data analysis technique used in this study was carried out using several methods, namely Validity Test, Reliability Test, Multiple Linear Regression Test and Income Test. From the research results it is known that the income of cocoa farmers in Padang Kamburi Village, Bupon District, Luwu Regency is strongly influenced by factors of production costs, cocoa prices, labor, and land area. The net income of cocoa farmers in Padang Kamburi Village, Bupon District, Luwu Regency is IDR 1,393,775.78 in one harvest.